Strategi Manajemen Risiko pada Kegiatan Pembelajaran Daring di Sekolah Dasar - Putri Utami, Anggun Ramadhani; Irsyad; Setiawati, Merika (CV. ITTC INDONESIA, 2025)
This research aims to provide solutions or strategies to address obstacles in online courage-based learning activities in elementary schools based on the implementation of risk management. In today's era, the use of technology is increasingly developing, one example of which can be implemented in the educational realm. Online learning has become popular since the Covid-19 pandemic, and it is still implemented in several schools. It is not uncommon for elementary schools (SD) in Indonesia to still use the courage method in the teaching and learning process. Implementing courage-based teaching and learning activities inevitably faces many risks and challenges, both from the students themselves, teachers, and parents. These risks can include technical and psychological challenges, participation issues, and data security issues. Therefore, courage-based learning activities involve many parties. This research collected literature data, mostly obtained from journal articles.